2022
DOI: 10.1186/s13104-022-06033-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of aortic valve pressure gradient quantification using semi-automated 4D flow CMR pipeline

Abstract: Objective Doppler echocardiographic aortic valve peak velocity and peak pressure gradient assessment across the aortic valve (AV) is the mainstay for diagnosing aortic stenosis. Four-dimensional flow cardiovascular magnetic resonance (4D flow CMR) is emerging as a valuable diagnostic tool for estimating the peak pressure drop across the aortic valve, but assessment remains cumbersome. We aimed to validate a novel semi-automated pipeline 4D flow CMR method of assessing peak aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…When compared to two-dimensional (2D) phase-contrast acquisition, 4D flow offers better visualisation of flow in the whole heart and great vessels. Also, it allows us to generate reformatted flow plane in the region of interest after scans [11][12][13][14]. This allows flexibility to explore flow patterns in more detail without the requirement of patient being in the scanner all the time.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to two-dimensional (2D) phase-contrast acquisition, 4D flow offers better visualisation of flow in the whole heart and great vessels. Also, it allows us to generate reformatted flow plane in the region of interest after scans [11][12][13][14]. This allows flexibility to explore flow patterns in more detail without the requirement of patient being in the scanner all the time.…”
Section: Introductionmentioning
confidence: 99%
“…Four-dimensional (4D) flow time-resolved phase-contrast cardiac magnetic resonance (CMR) with retrospective valve-tracking can provide a more comprehensive and multidirectional assessment of peak blood flow velocities across cardiac valves (4)(5)(6)(7)(8)(9). Previous studies have identified good agreement between 4D flow CMR and the reference method for peak flow velocity assessment, namely pulse-wave doppler TTE (5,6,7). Four-dimensional flow CMR can overcome many of the limitations of Doppler TTE and may improve the accuracy of transvalvular peak velocity quantification (2,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%